HIV-1 and BLV are insensitive to SERINC5 restriction under the cell-cell infection - Changqing Yu; Faming Jiang; Yujing Li; Qiushui Li; Kenzo Tokunaga; Dan Yang; Chao Xu; Nan Li; Sunan Li; Ilyas Khan; Yuanhua Xian; Changyou Xia; et al. (Microbiology Spectrum)
ABSTRACT Serine incorporator 5 (SERINC5, SER5) suppresses viral cell-free infection. However, its antiviral potency under viral cell-cell infection is not examined yet. Here, we established the in vitro cell-cell infection systems to assess SER5’s antiviral activity on HIV-1 and bovine leukemia virus (BLV). Our results showed SER5 from different mammalian species, including Homo sapiens, Bos taurus, and Felis catus, was capable of significantly inhibiting HIV-1 cell-free infection. However, these SER5s were unable to restrict HIV-1 cell-cell infection. Intriguingly, Ebola virus glycoprotein-mediated pseudoviral cell-free infection was greatly enhanced by Homo sapiens and Bos taurus SER5. Notably, BLV was also insensitive to SER5-mediated restriction under the cell-cell infection. In addition, BLV envelope glycoproteins, which contained one glycosylation variation, were not restricted by SER5 in the model of cell-cell infection. Overall, our results indicated SER5 was ineffective against HIV-1 and BLV under the cell-cell infection, which was utilized by them to circumvent SER5-imposed restriction in vitro and may aid their transmission in vivo.IMPORTANCESER5 potently inhibits virus infection under the cell-free mode. However, few studies check whether SER5 keeps its restriction under the virus cell-cell transmission. In this work, we uncover SER5 loses its restriction to HIV-1 and BLV under the mode of cell-cell infection, demonstrating the viruses could employ this mode to overcome SER5 restriction and thus facilitate their transmission.